One great speech : secrets, stories, and perks of the paid speaking industry (and how you can break in) - Reilly, James Marshall (Sourcebooks, 2020)
"Combining the career aspiration of The 4-Hour Workweek with the industry-specific insider take of Kitchen Confidential, One Great Speech is the first book to take readers inside the exciting world of the paid speaking industry. Aspiring speakers will find that, with the right know-how, anyone can harness the power of this career path. James Marshall Reilly demonstrates how the principles he used to generate millions of dollars in this fast-paced, high-pressure industry can be applied by anyone searching for paid speaking success. This industry has changed countless lives. With Reilly disclosing closely guarded industry knowledge, your life-changing moment could be here! Packed with engaging case studies, tips, and inside information on this largely unregulated industry, One Great Speech is the only complete resource that teaches you the ins and outs of the world of paid speaking"--